EXPLORING STUDENTS’ LEARNING STRATEGIES AND GENDER DIFFERENCES IN ENGLISH LANGUAGE TEACHING - Mahmud, Murni; Nur, Sahril (International Journal of Language Education, 2018)
The main objective of this paper is to explore the learning strategies of male and female students and to discuss those strategies in relation to gender differences. This research was conducted in one senior high school in Makassar, Indonesia. The number of respondents was 71 students taken randomly by using Slovin formula among 250 students. The study used quantitative and qualitative data. The quantitative data were collected by using a questionnaire of SILL whereas the qualitative data were taken by using interview. The learning strategies were discussed based on Oxford?s learning strategies (1990) whereas the notion of gender differences in relation to learning strategies was discussed in the framework of gender differences in communication proposed by Lakoff (1975, 1976) and (Tannen, 1990, 1994). Findings from the questionnaire show that female students use cognitive, compensation, and affective strategy more often compared to male students while male students use memory, metacognitive, and social strategy more often compared to female students. Findings from the interview show that female and male students chose different learning strategies. In addition, those learning strategies were influenced by the notion of gender differences in communication. These findings significantly give beneficial inputs to the process of English language teaching in order to create effective teaching and classroom interaction. It also provides significant contribution to the study on language and gender in communication in a setting of education and language teaching.